Local anaphor licensing in an SOV language: implications for retrieval strategies - Kush, Dave; Phillips, Colin (Frontiers in Psychology, 2014)
Because morphological and syntactic constraints govern the distribution of potential antecedents for local anaphors, local antecedent retrieval might be expected to make equal use of both syntactic and morphological cues. However, previous research (e.g., Dillon et al., 2013) has shown that local antecedent retrieval is not susceptible to the same morphological interference effects observed during the resolution of morphologically-driven grammatical dependencies, such as subject-verb agreement checking (e.g., Pearlmutter, Garnsey and Bock, 1999). Although this lack of interference has been taken as evidence that syntactic cues are given priority over morphological cues in local antecedent retrieval, the absence of interference could also be the result of a confound in the materials used: the post-verbal position of local anaphors in prior studies may obscure morphological interference that would otherwise be visible if the critical anaphor were in a different position. We investigated the licensing of local anaphors (reciprocals) in Hindi, an SOV language, in order to determine whether pre-verbal anaphors are subject to morphological interference from feature-matching distractors in a way that post-verbal anaphors are not. Computational simulations using a version of the ACT-R parser (Lewis and Vasishth, 2005) predicted that a feature-matching distractor should facilitate the processing of an unlicensed reciprocal if morphological cues are used in antecedent retrieval. In a self-paced reading study we found no evidence that distractors eased processing of an unlicensed reciprocal. However, the presence of a distractor increased difficulty of processing following the reciprocal. We discuss the significance of these results for theories of cue selection in retrieval.